Novel quantitative analysis of autofluorescence images for oral cancer screening. (May 2017) - Huang, Tze-Ta; Huang, Jehn-Shyun; Wang, Yen-Yun; Chen, Ken-Chung; Wong, Tung-Yiu; Chen, Yi-Chun; Wu, Che-Wei; Chan, Leong-Perng; Lin, Yi-Chu; Kao, Yu-Hsun; Nioka, Shoko; Yuan, Shyng-Shiou F.; et al.
Highlights: Developed quantitative analysis of autofluorescence images for oral cancer screen. Quadratic discriminant analysis was utilized to compute a boundary. Oral cancer and precancer lesions can be discriminated from normal oral mucosa. Abstract: Objectives: VELscope® was developed to inspect oral mucosa autofluorescence. However, its accuracy is heavily dependent on the examining physician's experience. This study was aimed toward the development of a novel quantitative analysis of autofluorescence images for oral cancer screening. Materials and methods: Patients with either oral cancer or precancerous lesions and a control group with normal oral mucosa were enrolled in this study. White light images and VELscope® autofluorescence images of the lesions were taken with a digital camera. The lesion in the image was chosen as the region of interest (ROI). The average intensity and heterogeneity of the ROI were calculated. A quadratic discriminant analysis (QDA) was utilized to compute boundaries based on sensitivity and specificity. Results: 47 oral cancer lesions, 54 precancerous lesions, and 39 normal oral mucosae controls were analyzed. A boundary of specificity of 0.923 and a sensitivity of 0.979 between the oral cancer lesions and normal oral mucosae were validated. The oral cancer and precancerous lesions could also be differentiated from normal oral mucosae with a specificity of 0.923 and a sensitivity of 0.970. Conclusion: The novel quantitative analysis of the intensity and heterogeneity of VELscope® autofluorescence images used in this study in combination with a QDA classifier can be used to differentiate oral cancer and precancerous lesions from normal oral mucosae.